Politicising Europe : integration and mass politics - Hutter, Swen <<[HerausgeberIn]>>; Grande, Edgar <<[HerausgeberIn]>>; Kriesi, Hanspeter <<[HerausgeberIn]>> (Cambridge University Press, 2016)
"Politicising Europe presents the most comprehensive contribution to empirical research on politicisation to date. The study is innovative in both conceptual and empirical terms. Conceptually, the contributors develop and apply a new index and typology of politicisation. Empirically, the volume presents a huge amount of original data, tracing politicisation in a comparative perspective over more than forty years. Focusing on six European countries (Austria, France, Germany, Sweden, Switzerland and the UK) from the 1970s to the current euro crisis, the book examines conflicts over Europe in election campaigns, street protests, and public debates on every major step in the integration process. It shows that European integration has indeed become politicized. However, the patterns and developments differ markedly across countries and arenas, and many of the key hypotheses on the driving forces of change need to be revisited in view of new findings"--
Literaturverzeichnis: Seite 314-334
5550,MK 5000:bvb